Pengaruh Minat terhadap Capaian Hafalan Al-Qur’an Siswa pada Program Tahfizul Qur’an di Madrasah Tsanawiyah Negeri 1 Banjarnegara - Muhammad Aflah Nurhuda; Nurul Mubin; Ahmad Zuhdi (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to explore how students’ interest plays a role in their ability to memorize the Qur’an in the Tahfizul Qur’an program at MTs Negeri 1 Banjarnegara. The study utilizes a descriptive qualitative approach, gathering information through observation, in-depth interviews, and documentation. Participants in this research include tahfiz students, tahfiz teachers, and the program coordinator. The data were processed and analyzed following Miles and Huberman’s framework, which involves phases of reducing data, displaying it, and drawing conclusions. The findings indicate that student interest positively and significantly affects their Qur’anic memorization achievements, both in terms of amount and quality. Higher interest is associated with more effective memorization. Additionally, this interest is influenced by internal factors, such as motivation and satisfaction, as well as external factors, including family and teacher support, all of which help foster a successful tahfiz learning process. The study underscores the necessity of developing and maintaining student interest to maximize the outcomes of the tahfiz program.